2017
DOI: 10.1007/s00404-017-4520-8
|View full text |Cite
|
Sign up to set email alerts
|

Therapy-free interval has prognostic value in patients with recurrent cervical cancer treated with chemotherapy following definitive concurrent chemoradiotherapy

Abstract: TFI has predictive value for response to chemotherapy and prognosis of patients with recurrent cervical cancer after definitive CCRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 20 publications
2
15
1
Order By: Relevance
“…The present study found that adverse events (thrombocytopenia, myelosuppression, hepatic or renal dysfunction) occurred more commonly in the radiochemotherapy group than in the DEB‐TACE group, suggesting DEB‐TACE has a comparative advantage in the context of safety profile . The incidence of complications, including postembolization syndrome, upper quadrant pain, fever, nausea, and vomiting, has also been reported to be much lower among HCC patients treated with DEB‐TACE than among those treated with conventional TACE .…”
Section: Discussionmentioning
confidence: 49%
“…The present study found that adverse events (thrombocytopenia, myelosuppression, hepatic or renal dysfunction) occurred more commonly in the radiochemotherapy group than in the DEB‐TACE group, suggesting DEB‐TACE has a comparative advantage in the context of safety profile . The incidence of complications, including postembolization syndrome, upper quadrant pain, fever, nausea, and vomiting, has also been reported to be much lower among HCC patients treated with DEB‐TACE than among those treated with conventional TACE .…”
Section: Discussionmentioning
confidence: 49%
“…However, patients eligible to receive third-line chemotherapy for recurrent cervical cancer can expect minimal benefits at the cost of significant toxicity (24). Other factors, such as the therapy-free interval, may influence the response to chemotherapy and the prognosis of recurrence after definitive CCRT (25).…”
Section: Discussionmentioning
confidence: 99%
“…The curative effect of traditional radiotherapy and chemotherapy is poor, and complications are obvious. The tolerance and quality of life of patients are poor [9][10][11]. Immunotherapy is the main treatment for recurrent cervical cancer, but its clinical application is greatly limited due to its high price.…”
Section: Discussionmentioning
confidence: 99%